PREVALENCE AND FACTORS INFLUENCING TUBERCULOSIS AMONG PEOPLE LIVING WITH HIV SEEKING HEALTH CARE AT THE ART CLINIC IN KAWAALA HEALTH CENTRE IV- KAMPALA DISTRICT. A CROSS-SECTIONAL STUDY. (Student's Journal of Health Research Africa, 2024)
Background  This study specifically assessed the prevalence of Tuberculosis among PLWHIV, the social and cultural factors, and the socio-economic factors contributing to the prevalence of Tuberculosis in HIV/AIDS in patients seeking health care in Kawaala Health Center IV in Kampala district.          MethodologyThe study adopted a cross-sectional research design with a quantitative approach to data collection where 96 respondents were conveniently sampled and data was gathered from them using questionnaires and self-administration questionnaire method of data collection. ResultsThe study established that out of 96 respondents, 10 (10.4%) had TB while 86 (89.6%) of the HIV patients studied did not have TB. Among the 10 who had TB, 07 (70%) were male and females were 03 (30%). The study further indicated that out of 96 respondents, 51 (53.1%) did not have a family history of TB however, 56 (58.3%) were active smokers and 63 (66%) did not drink alcohol but 50 (52.1%) of those who drank did so from the joints with their friends and 80 (83%) did not have any TB patient that they were closed to. The study also established that out of 96 respondents, 60 (62.5%) were unemployed of which 58 (60.4%) had an income level of below 200,000 shillings with 67 (70%) being rural residents. Conclusion The study therefore concluded that the prevalence of TB among HIV patients was high, most especially among male patients with the prominent socioeconomic factors being unemployment, income level of below 200,000 shillings, rural residency, and overcrowding while active smoking and drinking from the joints with friends were the prominent socio-cultural factors. RecommendationThe study recommends the government establish collaboration between TB and HIV programs which should be strengthened by creating a coordinating body to ensure very close collaborative activities to avoid leakages in the referral system for both programs.
Keywords: Tuberculosis; HIV; Art Clinic